An annotated checklist of the Greek Stonefly Fauna (Insecta: Plecoptera) - Karaouzas, Ioannis; Andriopoulou, Argyro; Kouvarda, Theodora; Murányi, Dávid (Zootaxa, 2016)
An overview of the Greek stonefly (Plecoptera) fauna is presented as an annotated index of all available published records. These records have resulted in an updated species list reflecting current taxonomy and species distributions of the Greek peninsula and islands. Currently, a total of 71 species and seven subspecies belonging to seven families and 19 genera are reported from Greece. There is high species endemicity of the Leuctridae and Nemouridae, particularly on the Greek islands. The endemics known from Greece comprise thirty species representing 42% of the Greek stonefly fauna. The remaining taxa are typical Balkan and Mediterranean species.